PEMBINAAN KARAKTER RELIGIUS SANTRI DI MUHAMMADIYAH BOARDING SCHOOL YOGYAKARTA - Putri Amilosa; Sumedi Sumedi (Universitas Muhammadiyah Ponorogo, 2018)
The background of this research is the education and development which show and develop about religious attitude as the bridge to internalize Islamic knowledge in the daily life. The character development is needed to every teacher for creating how Islamic education can be the base of life in daily activity.A boarding school with it's background and culture to be place which researcher try to know about their model of religious character for studen and implementation. This research is a qualitative field research by taking background of Muhamamdiyah Boarding School Yogyakarta. This research is a character education approach. Subject of this research such as Directors, teachers, students of Muhammadiyah Boarding School Yogyakarta. The data collecting has done by conducting a sociological dan psychological approach. Methods of thinking in the analysis of data research is inductive by collecting and combing special words into a unified information. The results show that the character building model used by Muhammadiyah Boarding School Yogyakarta is by using pesantren system and the teaching of Islamic sciences which directly regulate the dynamics of santri to have good religious character such as being kind people, polite, responsible, and diligent to worship.